Anatomical and Physiological Variations in Certain Selected Species and Provenances of Acacia - Santhosh Jacob (Department of Tree Physiology and Breeding, College of Forestry, 2001)
An experiment was carried out during 1998-99 with the objective of evaluating the anatomical and physiological variations among provenances and species of Acacia and to correlate this with their growth characteristics. The experimental materials consisted of 11 provenances which included five provenances of Acacia mangium Willd., and two each of A. auriculiformis Cunn. ex., Benth., A. crassicarpa Cunn ex., Benth and A. aulacocarpa Cunn. ex., Benth. They were planted in a randomized block design in the farms of the College of Forestry, Vellanikkara in 1996. The ultimate objective of the study was to identify the most suitable species/provenances from among these for the ecoclirnatic conditions ofKerala. At four years of growth, provenances Balimo Aramia and Wipim to Oriomo from Papua New Guinea and Research Seed Orchard from Queensland were significantly superior to the rest. Among the four species, except A. aulacocarpa, the other three species namely, A. mangium, A. auriculiformis and A. crassicarpa showed superiority over height and collar girth. The most important component of total biomass undoubtedly, was the bole volume. So in this regard, the superiority of the species on height and collar girth indicates good volume production in future. A. auriculiformis exhibited superiority over branch production throughout the study, indicating its suitability for fire wood production. As far as leaf area is concerned the species exhibited significant . variation while, provenances did not. A. mangium and A. aulacocarpa showed maximum leaf area index, compared to A. auriculiformis and A. crassicarpa.